2017
DOI: 10.1097/coc.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Does Choline PET/CT Change the Management of Prostate Cancer Patients With Biochemical Failure?

Abstract: These early results suggest that labeled choline PET/CT imaging performed according to current NCCN guidelines may change management and improve care in prostate cancer patients with biochemical failure by identifying patients for referral for salvage radiation therapy, improving radiation planning, and delaying or avoiding use of androgen deprivation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…In daily clinical practice, choline PET/CT has been shown to be of value in patient management, leading to a change in the management decision in approximately 50 % of patients [27][28][29]. However, despite a wide bibliography [23,26], there is still no consensus as to the proper indication for choline PET/CT in patients with BCR.…”
Section: Discussionmentioning
confidence: 97%
“…In daily clinical practice, choline PET/CT has been shown to be of value in patient management, leading to a change in the management decision in approximately 50 % of patients [27][28][29]. However, despite a wide bibliography [23,26], there is still no consensus as to the proper indication for choline PET/CT in patients with BCR.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 43 studies, 13 were excluded: patients without biochemical relapse but with advanced disease or assessed for primary staging, i.e. inclusion criteria not fulfilled (3 studies [17][18][19]); intervention not in the inclusion criteria (1 study [20]); outcome of interest not reported (4 studies [21][22][23][24]); and no reference standard reported (5 studies [25][26][27][28][29]). Finally, 29 studies with 2,686 participants were included (Fig.…”
Section: Bibliographic Searchmentioning
confidence: 99%
“…This is lower than in other studies, which showed a change of treatment plan in 48-55% of patients. 23,24 These studies used retrospective questionnaires completed by treating physicians and were not blinded, in contrast to our study. This could possibly explain the difference between results.…”
Section: Discussionmentioning
confidence: 73%
“…16 Choline is an essential component of phospholipid membrane and demonstrates increased metabolism in PCa. 17 The limited short half-life of 11C-choline (20.3 [23][24][25] The primary objective of this study was to determine predictive factors (patient and PSA characteristics) for 18F-FCH PET/CT positivity in patients with biochemical failure after local treatment for PCa with curative intent. Secondary objectives were to evaluate the impact of PET/CT on patient management and to compare its value to standard imaging techniques.…”
Section: Introductionmentioning
confidence: 99%